???? ???? ???? Triticum aestivum . L????? ????? ??? ???? ?? ????? ???? ????? ??????????? ????? ????? - زهير راضي (مجلة علوم ذي قار, 2019)
An experiment was conducted in side the lath house. On three genetic structures  (3.37 Maxiback, 3.41 Abu – Grab – 3 and ACTED) to study the different salt levels of NaCl and CaSO4 in seed germination coefficient and some vegetative growth characters such as. Plant height, dry weigh number of tillers and total chlorophyll content of leaves. The result showed significant differences among the three genetic structures in all growth characters studied. 3.37 Maxback was superior compare to the other genetic structures. All salt levels reduced significantly all growth criteria studied was the 6 dc/m NaCl .Most effective treatment. Genetic structures differ in their salt tolerance ability. 3.37 Maxback and ACTED were more tolerant at compare to 3.41 Abu- Grab -3 .